THE EFFECTIVENESS OF PROBLEM SOLVING LEARNING MODEL ON BUFFER SOLUTION AND HYDROLYSIS MATERIAL IN INCREASING OBESRVATION AND INTERPRETATION COMPETENCES - usep suhendar; chansyanah diawati; noor fadiawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The objectives of this research were to find out the effective learning model in increasing observation and interpretation competencies on buffer solution and hydrolysis subjects.  Observation and interpretation competencies were part of science process competency (SPC).  In line with the objectives of the research, problem colving learning model was applied in learning that is part of constructivism approach. The research method was experiment quasi with the non equivalence control group design.  By using purposive sampling technique the sample of this research was XI IPA 1 and XI IPA 3 class. Based on the calculation of hypotesis testing, the result of this research were; (1) problem solving learning model was effective in increasing observation competency (2) problem solving learning model was effective in increasing interpretation competency. Keywords  : observation competency, interpretation competency, problem solving                     model